Penentuan Pola Penindakan Pelanggaran Lalu Lintas di DKI Jakarta Menggunakan Metode Analytic Network Process (ANP) - Ramadhan, Idrus; Kurniawan, Avip; Syah Putra, Arman (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2020)
In this study, the authors raised the research problem in the field of traffic, especially in the field of traffic control and enforcement on roads, with a system of monitoring and enforcement that continues to develop, the proposed system will continue to exist in order to develop a more modern surveillance and enforcement system. The method used in this research is by using the literature review method or in other words looking at the latest books and journals in order to find new problems that can be raised in a study, the problems raised are very recent and use the right method. The application of the Analytic Network Process (ANP) method has been widely applied in various developed countries, because the system can provide the results of an analysis that is generated from the data obtained, with the Analytic Network Process (ANP) method which will greatly assist the police in the process of monitoring and enforcement in making a ticket penalty decision. In this study, the authors carry out research on the application of the Analytic Network Process (ANP) method in the traffic violation prosecution process that can be applied in the capital city of DKI Jakarta, the Analytic Network Process (ANP) method helps the system decide on ticket penalties for traffic rule violators.